Transcriptomic Profiling of SLC and ABC Transporters in the Human Term Placenta - Elijah Marsh Jung; Nicholas Ieronimakis; Bothaina Mousa; Emily D. Sheikh; Sarah E. Ligon; Joshua W. Monson; Jennifer R. Damicis; Hillary J. Kinsman; Lydia E. Bettridge; Samuel L.M. Arnold; Edward J. Kelly; Jashvant D. Unadkat; et al. (Clinical Pharmacology & Therapeutics, 2026)
Solute carriers ( SLC ) and ATP‐binding cassette ( ABC ) transporters are essential for placental solute exchange and fetal protection, yet their transcriptomic profiles in the human placenta remain poorly characterized. Although fetal sex influences placental development and function, its impact on transporter expression is unclear. Using RNA sequencing, we profiled SLC and ABC transporter expression in two anatomical regions of term human placentas ( N = 10) with balanced fetal sex distribution and controlled clinical features. In the intervillous region, 276 SLC s were detected, with 60% expressed at low levels (CPM < 25) and 110 (40%) expressed at higher levels (CPM 25–1650). Four transporters— SLC2A1 (GLUT1), SLC44A2 (CTL2), SLC38A2 (SNAT2), and SLC38A1 (SNAT1)—showed the highest expression (CPM > 500). Functional annotation of 110 SLC s revealed transporters for amino acids, metals, and inorganic ions each accounted for ~9%. Other well‐represented SLC s included xenobiotic and vitamin transporters. Mitochondrial, lysosomal, and endoplasmic reticulum and Golgi transporters together accounted for ~37%, while 11% were orphan transporters. Thirty‐seven ABC transporter transcripts were detected, primarily associated with xenobiotic and lipid transport. Compared with the intervillous region, 1676 genes—including 32 SLC and 2 ABC transporters—were differentially expressed in the decidual region. Although 117 genes in the intervillous region and 79 genes in the decidual region exhibited sexually dimorphic expression, none were SLC s. Notably, male placentas showed higher expression of ABCB1 (P‐gp), confirmed by qPCR and western blot. Our findings provide a transcriptomic map of placental transporters and highlight a potential sex‐specific difference on ABCB1 expression and xenobiotic protection.